Pengaruh CR dan DER terhadap ROE pada Perusahaan Makanan dan Minuman Tahun 2015-2018 - Julia Loviana Pratiwi; Benny Barnas; Fifi Afiyanti Tripuspitorini (Indonesian Journal of Economics and Management, 2021)
In this Final Project, the title "Influance of CR and DER on ROE in Food & Beverage in 2015 - 2018". The problems in this Final Project is how the effect of CR and DER variables on ROE in the period 2015 to 2018 seen relation and how big the influence of CR and DER on ROE. This research purpose is to find out the correlation between variable of CR and DER with ROE and the influence between the correlation. The research used descriptive analysis method and verificative analysis method. The results of the analysis show that the CR variable has a significant positive effect on the ROE variable with a significance level of 0.007, while the DER variable has no significant effect on ROE with a significance level of 0,196. While simultaneous CR and DER variables affect ROE with a coefficient of determination of 23% .